Ulam-Hyers Stability for MKC Mappings via Fixed Point Theory. (25th May 2016) - Hassan, Anisa Mukhtar; Karapınar, Erdal; Alsulami, Hamed H.
Abstract : We consider some extension of MKC mappings in the framework of complete dislocated metric spaces. Besides the theoretical results, we also consider some illustrative examples. Further, we state and prove that our main results improved the related results in the frame of generalized Ulam-Hyers stability theory.